ELOQUENCE IN TEACHER'S PROFESSIONAL TRAINING THE IMPORTANCE OF PERFORMANCE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this article, the fact that speaking ability is an art in the teacher's professional skills, that famous scientists have become one of the leading problems in scientific research, its current situation, the need for development, and the modern point of view are analyzed.  The author emphasized how important it is for the teacher to master the secrets of the art of public speaking in his pedagogical work, and highlighted the ways to further improve it.